FROM DOMESTIC TO INTELLECTUAL: TRANSFORMATION OF INDIGENOUS WOMEN'S EDUCATION THROUGH THE WIFE SCHOOL FOUNDED BY DEWI SARTIKA - Desma Febrianti (Journal of Learning on History and Social Sciences, 2024)
This research aims to analyze the role of Dewi Sartika in the transformation of indigenous women's education at the beginning of the 20th century through the establishment of Saolah Istri. The main focus of the research is to examine the background of the school's founding, its development, and its impact on society. The research method used is the historical method, including heuristics (source search), source criticism, interpretation, and historiography. The sources used are mainly secondary sources, including writings about Dewi Sartika and the history of education in Indonesia. The research results show that Saolah Istri, which was founded by Dewi Sartika in 1904, faced initial challenges but developed rapidly into the Kautamaan Istri School. This school plays an important role in opening access to education for women from various social backgrounds. A curriculum that combines practical skills and academic knowledge prepares graduates to become independent individuals and contribute to society